Innovation and national innovation system that are being formed - Nguyen Phuong Tuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
The article introduces the concept and basic connotations of Innovation and analyzes the use of the term “Innovation” to ensure correct (accurate) use in research as well as in administration and management. After a summary of the concept, constituent elements and activities of the National Innovation System, some concepts about other “systems” and “ecosystems” are presented additionally to clarify the differences between these types. In the final part, the article analyzes the characteristics of the National Innovation System being formed in developing countries, then identifies some common structural problems and determines the role of the state in building the foundation for the NIS in Vietnam in the near future Code: 23102701